Respuesta :

Answer:

only Katie is right

Step-by-step explanation:

first, find the nth rule using the equation n = a + (n - 1)d

a = first term (here, it's 22)

n = the position of a term

d = the constant difference between each term (here, it's -5 since each term reduces by 5)

put these in and then simplify:

n = a + (n - 1)d

n = 22 + (n - 1)(-5)

n = 22 - 5n + 5

n = -5n + 27

this can be rewritten as n = 27 - 5n, which means therefore that only Katie is right. hope this helps!

Answer: Only Katie

Reason: Only Katie is correct!